Pengaruh Pendekatan Contextual Teaching and Learning (CTL) dalam Pembelajaran Kooperatif Tipe Jigsaw terhadap Hasil Belajar Fisika Siswa Kelas X SMAN 4 Palu - Lestari Taruk Datu; Amiruddin Kade (Jurnal Kreatif Online, 2021)
The study aimed to determine the effect of the CTL approach in Jigsaw type cooperative learning on physics learning outcomes for tenth-grade students of SMAN 4 Palu. This type of research was quasi-experimental. The research population was the students of class X IPA SMA Negeri 4 Palu. The sampling technique used in this study was purposive sampling, with the research sample being class X IPA 4 as the experimental group and X IPA 3 as the control group. The instrument for learning physics was in the form of a multiple-choice test. Testing of student learning outcomes data using t-test statistical analysis with prerequisites, namely normality test and homogeneity test. The results of data analysis obtained that the average value of the experimental group was 15.08 with a standard deviation of 8.69 and the average value of the control group was 12.06 with a standard deviation of 8.48. Based on hypothesis testing with t-test statistics, it was obtained tcount = 4.25 and ttable = 1.67 at a significance level of = 0.05. This result means that the value of tcount is outside the area of ​​acceptance of H0. So, it can be concluded that there is an effect of the CTL approach in Jigsaw type cooperative learning on physics learning outcomes of tenth-grade students of SMAN 4 Palu.